1989
DOI: 10.1063/1.456870
|View full text |Cite
|
Sign up to set email alerts
|

Resonant two-photon ionization-photoelectron spectroscopy of Cu2: Autoionization dynamics and Cu+2 vibronic states

Abstract: Resonant two-photon ionization of gas phase CU 2 in a cold molecular beam in conjunction with time-of-flight photoelectron spectroscopy provides new vibronic state spectroscopic infonnation for the dimer cation Cu 2 + . One color ionization via the 0-0, 1-0, and 2a-O bands of Smalley's System V neutral CU2 resonant states (J ..... X transition) accesses Cut states in the range 0-1.4 eV. The electron kinetic energy measurements slightly refine the first adiabatic ionization energy ofCu 2 to II (Cu 2 ) = 7.899 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…In the majority of studies reported here, this UV probe pulse was fixed to be resonant at the one-photon level with the J (v = 0) ' X (v = 0) transition in 63 Cu 2 (previously Smalley's ''system V'') 11 at 267.06 nm. 1,21 In two-colour experiments, especially in the study of CuO, a second pump pulse, comprising the signal output of a 355 nm pumped optical parametric oscillator (Continuum Panther) is arranged to co-propagate with the UV beam and fires typically 30 ns before the probe. This delay is sufficient to permit resolution of visible only and true twocolour processes in the time-of-flight spectrum which proved useful in simplifying the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the majority of studies reported here, this UV probe pulse was fixed to be resonant at the one-photon level with the J (v = 0) ' X (v = 0) transition in 63 Cu 2 (previously Smalley's ''system V'') 11 at 267.06 nm. 1,21 In two-colour experiments, especially in the study of CuO, a second pump pulse, comprising the signal output of a 355 nm pumped optical parametric oscillator (Continuum Panther) is arranged to co-propagate with the UV beam and fires typically 30 ns before the probe. This delay is sufficient to permit resolution of visible only and true twocolour processes in the time-of-flight spectrum which proved useful in simplifying the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This process has been studied in detail by Sappey et al using photoelectron spectroscopy (PES). 20,21 The Cu 2 + spectrum is mirrored approximately in the Cu + channel indicating a significant degree of photofragmentation. By way of investigating the likely fragmentation mechanism(s) involved we have recorded one-colour VMI images at this wavelength and the resulting total kinetic energy release (TKER) spectrum is shown in the lower portion of the Fig.…”
Section: Cu 2 + Uv Photoionization and Photodissociationmentioning
confidence: 99%
See 1 more Smart Citation
“…u state by the rotational P(10) transition from the electronic ground state, (b) is obtained by exciting the band origin v ′ = 0 by P (10), and (c) shows the energy diagram and transitions involved for the UNFOLDED two-color resonant four-wave mixing scheme. Δ indicates the energy interval between levels of B0 + u v ′ = 1 J ′ = 9 and B0 + u v ′ = 0 J ′ = 9 0 + g state from v ′ = 0 by the UNFOLDED double-resonance scheme, the P(9) and R(9) transitions are expected to occur in a wavenumber region shifted by +241.81 cm −1 , which is the energy difference of the v ′ = 1 and v ′ = 0 levels in the B0 + u state.…”
Section: Figurementioning
confidence: 99%
“…By opening the d-shell upon excitation of an electron, a complex electronic configuration is obtained that is typical for transition metals thus providing an unique opportunity to understand the role of the d-orbitals in chemical bonding. [1,2] As such, extensive experimental [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and theoretical work [19][20][21][22][23][24] have focused on the ground and excited electronic levels of Cu 2 . The electronic ground state has been identified as X 1 Σ + g state in Hund case (a) notation.…”
Section: Introductionmentioning
confidence: 99%